A Multi-Scale analysis of organochlorine pesticide contamination in raptor populations: research effort, historical trends, and current concentrations - Padayachee, Kailen (Department of Biological Sciences, 2026)
Pesticide contamination and the associated impacts on biodiversity, have been the focus of intense research and tremendous concern for environmental and conservation scientists over many decades. The environmental consequences of organochlorine pesticides, particularly Dichlorodiphenyltrichloroethane's (DDT) were made famous by Rachel Carson's book, Silent Spring in the early 1960s. Their impacts on environmental and human health were subsequently widely recognised and led to their bans and/or restricted use. DDT and dieldrin are two of the most infamous pesticide compounds ever manufactured, being included on a list of organochlorine pesticides (OCP) of global concern by the Stockholm Convention on Persistent Organic Pollutants (POPs). Their effectiveness in controlling pest species has come with a considerable negative impact on the global environment. These OCPs have consequently been strictly controlled and managed globally by various legislation, treaties, and conventions, some of which have been in place for many decades. These bans and restrictions have led to a decline in the production and use of DDT and dieldrin throughout most parts of the world. However, despite their bans, or in the case of DDT, strict restrictions on use, have their levels fallen or are they still present in the environment at elevated levels because of their persistent nature? The biomagnification of DDT and dieldrin in the environment, at higher trophic levels is well documented in the literature. These pesticides are ingested by potential prey species at lower trophic levels, which consume contaminated vegetation, water, or invertebrates. These prey species are then subsequently consumed by species at higher trophic guilds and then ultimately by apex predators. The concentrations of these pesticides consequently increase in tissues of organisms at successively higher levels of the food chain. This process of bioaccumulation and biomagnification means that species at higher trophic levels, like raptors, can act as valuable indicators of environmental pollutants. Raptors are quintessential apex predators, occupying top levels of the food chain in various ecosystems globally. Due to the well-known negative impacts of these pesticides on global raptor populations, this group of predatory birds have played an invaluable role as sentinel species in the monitoring of DDT and dieldrin contamination in both aquatic and terrestrial ecosystems. Consequently, raptors may be a prime candidate to undertake a comprehensive global-scale assessment to evaluate the extent of DDT and dieldrin monitoring and to assess whether the implementation of worldwide bans has led to a decline in these pesticide levels. Chapter 1 of this thesis introduces pesticides and the pivotal role they played in the success of humankind over centuries. I discuss the various natural, benign pesticides developed throughout history and how these pesticides gradually advanced into more powerful, synthetic chemicals such as DDT and dieldrin. I demonstrate that while these chemicals did offer an undeniable benefit to humankind, compelling evidence began to surface uncovering the more harmful effects of these chemicals on both environmental and human health. I outline the history of these chemicals and delve into how these pesticides were used in different contexts. Chapter 1 concludes by demonstrating how, over time, raptors became an invaluable group of sentinel species for monitoring these pesticides in various ecosystems. In Chapter 2, I explore DDT and dieldrin monitoring in raptors globally over time and space. Through reviewing the multitude of published studies assessing DDT and dieldrin in raptors, I describe the patterns in global research effort focused on the evaluation of these pesticides in raptors. This monitoring spans from the widespread use of these pesticides in the 1950s to the period following the implementation of worldwide restrictions. I then contrast these patterns of monitoring between regions, species, and time, describing how the biases uncovered in this thesis are yet another example of the inequality in scientific knowledge production between the Global North and Global South. In Chapter 3, I assess the efficacy of local legislation and international agreements to manage environmental contamination by DDT. I once again used the abundance of published literature to describe the spatial and temporal patterns in DDT concentrations in raptors across the globe, specifically looking at contamination levels in the most commonly sampled tissues following local bans and restrictions in DDT use across the globe. I not only describe how concentrations of this pesticide have changed over time but also how these levels and changes differ amongst environments. I demonstrate a clear decline in DDT in the Global North, while demonstrating how the lack of monitoring in the Global South has led to insufficient data to assess whether declines are globally representative. I also found that rates of decline depend on variables such as precipitation, and dietary guild. The declines in the Global North, provide hope that legislation and mitigation efforts, in concert with increased monitoring in the Global South, may benefit this region. Thus, the key finding from this chapter, is the welcome demonstration that local legislation and international agreements, when implemented correctly can efficiently halt environmental contamination. The Montreal Protocol is another such example that helped reduce the depletion of the ozone layer, curbing harmful solar ultra-violet radiation by banning chemicals such as CFCs (chlorofluorocarbons). These success stories provide hope that other global crises such as climate change and biodiversity loss can benefit from well planned and implemented local and global agreements. Furthermore, the benefits of using raptors as biomonitors of pesticides and other dangerous contaminants has been well documented, particularly in the Global North. Decades of using raptors as sentinels have played a crucial role in shaping international conventions like the Stockholm Convention by providing essential information on the harmful effects of contaminants on the environment and humans. Given the reduced concern about these contaminants, especially in the Global North, and limited data from the Global South, Chapter 4 examined contemporary DDT and dieldrin levels in a single raptor species. Various tissues were sampled from multiple migratory Amur Falcons (Falco amurensis), collected during a mass mortality event at two roost sites in the KwaZulu-Natal Province of South Africa. The analysis of these migratory falcons was only the second study conducted in a country of the Global South, allowing restricted use of DDT, post the 2006 reintroduction of this pesticide. It, therefore, actively addresses some of the knowledge gaps identified in Chapter 2 (namely the lack of data on DDT and dieldrin concentrations from the Global South). The concentrations of DDT detected in these falcons were generally low, echoing the downward trend in Global North DDT contamination described in Chapter 3. However, two fat samples exhibiting the highest DDT concentrations in the last two decades suggest cause for caution in the face of limited Global South data. This work also directly contributes to the limited toxicological data available for Amur Falcons in particular, representing the first samples of DDT and dieldrin concentrations in this species to my knowledge. While this study found low DDT concentrations in these migratory raptors, the dieldrin concentrations were indicative of a potential worrying, recent exposure to a pesticide that has been completely banned globally since the late 1980s. Chapter 5 of this thesis ties together all the chapters and synthesises the key findings from each of them. It provides a global perspective on the decline in DDT and dieldrin in raptors, taking into consideration the considerable geographic bias in research on this topic towards the Global North. It also highlights the efficacy of international agreements and local legislation and implementation in addressing and curbing global issues such as OCP contamination of the environment. This final chapter also discusses that, while contemporary DDT levels generally echo historical measurements, they may not necessarily confirm a global decline in this pesticide. I conclude this chapter by exploring potential future research opportunities that have emerged as a result of this thesis. This thesis provides the first global-scale review of how DDT and dieldrin has been studied and assessed in raptors, providing direct evidence that DDT concentrations in the Global North are declining. This suggests that legislation in this region has been largely successful in mitigating environmental contamination by this pesticide. However, insufficient data from the Global South post the 2006 DDT reintroduction affirms the bias in monitoring and research to the Global North. Furthermore, it highlights an urgency to generate sufficient data from countries still using DDT in order to assess whether the decline in DDT can be regarded as globally representative. It is tempting to suggest that low contemporary concentrations of DDT in a raptor wintering in a country with restricted DDT use supports the notion that DDT may also be declining in the Global South. However, the record high concentrations in fat from two individuals may indicate the contrary, that declines in the Global North do not necessarily translate to declines in the Global South. The dieldrin concentrations found in Amur Falcons in South Africa, also raises concern that there may be illegal and illicit use of a banned pesticide in South Africa. This result necessitates an urgent need to monitor dieldrin in KwaZulu-Natal, South Africa. By combining my findings across the chapters, I provide robust evidence that local findings further indicate an urgent need to improve monitoring of DDT and dieldrin in the Global South in order to determine whether declines in these pesticides from the Global North can be considered globally representative.